The human CD8 coreceptor effects cytotoxic T cell activation and antigen sensitivity primarily by mediating complete phosphorylation of the T cell receptor zeta chain. - Purbhoo, M; Boulter, J; Price, D; Vuidepot, A; Hourigan, C; Dunbar, P; Olson, K; Dawson, S; Phillips, R; Jakobsen, B; Bell, J; Sewell, A (2001)
Recognition of antigen by cytotoxic T lymphocytes (CTL) is determined by interaction of both the T cell receptor and its CD8 coreceptor with peptide-major histocompatibility complex (pMHC) class I molecules. We examine the relative roles of these receptors in the activation of human CTL using mutations in MHC class I designed to diminish or abrogate the CD8/pMHC interaction. We use surface plasmon resonance to determine that point mutation of the alpha3 loop of HLA A2 abrogates the CD8/pMHC interaction without affecting the affinity of the T cell receptor/pMHC interaction. Antigen-presenting cells expressing HLA A2 which does not bind to CD8 fail to activate CTL at any peptide concentration. Comparison of CTL activation by targets expressing HLA A2 with normal, abrogated, or diminished CD8/pMHC interaction show that the CD8/pMHC interaction enhances sensitivity to antigen. We determine that the biochemical basis for coreceptor dependence is the activation of the 23-kDa phosphoform of the CD3zeta chain. In addition, we produce mutant MHC class I multimers that specifically stain but do not activate CTL. These reagents may prove useful in circumventing undesirable activation-related perturbation of intracellular processes when pMHC multimers are used to phenotype antigen-specific CD8+ lymphocytes.